Moral Message on Banten Folklor and its Learning Proses of Character - Oriented at Elementary School - Suprani, Suprani (Opción, 2019)
The background of problem of this research was occurred due to the students’ lack of identifying of its folklore (Banten’s Folklore), the result of learning process of moral message analysis was only focused on knowledge, and it did not give any significant effect towards students’ behaviour and characters. The formulation of problem for this research were : (1) is there any moral message of Banten’s folklore (2) can learning process of Banten’s folklore be described through character education-oriented . this research was conducted through qualitative descriptive method. Meanwhile the data collecting tech- nique were conducted through test and non-test by using observation. The result of the research showed that the analysis or moral message on Banten’s folklore entitled “Oath mosque of Inland Terate” reached 6.20 ( f a i r l y good), on “Legend of Pinang Mountain” reached 7.45 (good), and on “The Legend of Kuwung Stone” reached 8.00 (very good), and those stories could be concluded contained the moral message. The result of observation showed that character education-oriented gave significant effect towards students’ at- titudes and behaviour. From the research could be concluded that Banten’s Folklore had its own moral message. The learning process of character edu- cation-oriented gave significant effect towards students’ behaviour, and it also could be applied in their daily life.